Syringomatous tumor of the nipple: master of deceit - Chauhan, Pooja; Sharma, Renu (International Journal of Research in Medical Sciences, 2025)
Syringomatous tumor (SyT) of the nipple is a locally infiltrative, benign neoplasm known to rarely involve breast. It usually presents as a unilateral retroareolar mass and may be associated with pain, nipple discharge or inversion. Microscopically tubules and ducts with comma-like configuration lined by double layered epithelium along with keratinizing cysts are seen similar to cutaneous adnexal neoplasm of eccrine origin. Since it shows infiltration into smooth muscle and nerves on microscopy, it is prone to be misdiagnosed as invasive carcinoma of breast. Initial management of SyT of the nipple requires complete resection of the lump with negative histological margins as this tumor is known to reoccur if incompletely excised. So, awareness of this entity is helpful when dealing with retroareolar breast lump clinically, radiologically and histologically. We present a case of SyT reported on a Tru-cut biopsy specimen in a 40 year old female presenting with retroareolar lump, for being a rare entity in breast and a diagnostic dilemma.